2020
DOI: 10.1016/j.jsxm.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The Vulvodynia Experience Questionnaire: Qualitative Development of a New Patient-Reported Outcome Measure for Vulvodynia

Abstract: Introduction Vulvodynia is defined as vulvar pain of at least 3 months duration without a clear identifiable cause. There are currently no validated questionnaires that assess the experience of women with localized vulvodynia of the vestibule (vestibulodynia, previously known as vulvar vestibulitis) that meet the requirements of the Food and Drug Administration's Patient Reported Outcome (PRO) Guidance. Aim To develop a new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A systematic review of trials for the symptoms of GSM revealed 49 different outcomes, with both patient-reported and clinician-measured outcomes being measured in a wide range of ways and different combinations 6 . Based on the patient-reported GU outcomes prioritized in the COMMA process, recommended measurement scales for GU symptoms include the Vulvovaginal Symptoms Questionnaire 27 and the Day-to-Day Impact of Vaginal Aging Questionnaire 28 . These questionnaires use agreed criteria and subcategories, with a threshold score/visual analog scale defining elevated symptoms.…”
Section: Suggestions For a Way Forwardmentioning
confidence: 99%
“…A systematic review of trials for the symptoms of GSM revealed 49 different outcomes, with both patient-reported and clinician-measured outcomes being measured in a wide range of ways and different combinations 6 . Based on the patient-reported GU outcomes prioritized in the COMMA process, recommended measurement scales for GU symptoms include the Vulvovaginal Symptoms Questionnaire 27 and the Day-to-Day Impact of Vaginal Aging Questionnaire 28 . These questionnaires use agreed criteria and subcategories, with a threshold score/visual analog scale defining elevated symptoms.…”
Section: Suggestions For a Way Forwardmentioning
confidence: 99%